Expanding the meaning of 'being a peer leader': qualitative findings from a Canadian community‐based cervical and breast cancer screening programme. (24th April 2016) - Ahmad, Farah; Ferrari, Manuela; Moravac, Catherine; Lofters, Aisha; Dunn, Sheila
Abstract: Engagement of community members to act as peer workers is a key feature of many community‐centred health promotion programmes. However, little is known about their experiences beyond the commonly reported themes of fulfilment through helping people in need and improvement of personal confidence, self‐esteem and self‐care. This gap in the literature is of particular interest given increasing involvement of peer workers in community‐centred programmes addressing health disparities, such as uptake of cancer screening. This paper aims to explore experiences of the peer leaders who worked for the Cancer Awareness: Ready for Education and Screening (CARES) project to promote awareness, knowledge, and uptake of breast and cervical cancer screening among under‐/never‐screened women who belonged to ethnic minority, recent immigrant and low‐income communities in Toronto, Canada. In 2013, three focus groups were conducted with 14 peer leaders to explore their experiences. All were immigrant women between 30 and 50 years of age. All discussions were audio recorded and transcribed verbatim. We used situational maps and analysis to create a visual representation of the data, and to investigate peer leaders experiences. Situational analysis was chosen to bring to light dominant and also silent underlying aspects which define the meaning of being a peer leader. The first level of analysis identified main themes that characterised peer leaders' experience: (i) Helping others (women, friends and family) and themselves by improved self‐confidence, self‐awareness and self‐care and (ii) Redefining professional and social positions through their project activities leading to professional development and networking. The second level of analysis explored the redefining process and identified some peer leaders' negotiations in relation to knowledge (science vs. myth), beliefs (fear vs. assurance) and boundaries (private vs. work). Adding to the literature on the peer workers' experience, the findings are discussed in relation to empowerment of peer workers, training implications and theoretical contributions.